A Common Fixed Point Theorem in Fuzzy Metric Spaces with Nonlinear Contractive Type Condition Defined Using Φ-Function. (11th March 2013) - Ješić, Siniša N.; Babačev, Nataša A.; Nikolić, Rale M.
Abstract : This paper is to present a common fixed point theorem for two R -weakly commuting self-mappings satisfying nonlinear contractive type condition defined using a Φ-function, defined on fuzzy metric spaces. Some comments on previously published results and some examples are given.